Investigating the effect of food additive dye “tartrazine” on BLG fibrillation under in-vitro condition. A biophysical and molecular docking study - Nasser Abdulatif Al-Shabib; Javed Masood Khan; Ajamaluddin Malik; Md Tabish Rehman; Mohamed F. AlAjmi; Fohad Mabood Husain; Aqeel Ahmad; Priyankar Sen (Journal of King Saud University: Science, 2020)
Tartrazine (Tz) is a yellow food color dye that is used in a range of foods to make them more appealing and attractive. However, very limited information is there about its interaction with macromolecules, like different proteins that are components of the food products. In this work the bovine beta-lactoglobulin (BLG) aggregation stimulating properties of Tz have been studied at pH 2.0. Spectroscopic, microscopic and molecular docking have been used to characterize the aggregation inducing property of Tz in BLG protein at pH 2.0. The spectroscopic techniques i.e., turbidity and RLS measurements showed that the 0.1–10.0 mM of Tz induces aggregation in BLG at pH 2.0. The aggregates were found to have well defined amyloid-like morphology as observed by CD and TEM. The amyloid fibrils were found long, straight and unbranched. Molecular docking results ascertained that Tz binds at the hydrophobic cavity and interact with the key amino acid residues involved in the interaction with different ligands. The spectroscopic, microscopic and computational results support that the electrostatic, as well as hydrophobic interactions, played a very important role in Tz-induced BLG fibrillation. Keywords: Tartrazine, Beta-lactoglobulin, Food additive dye, Amyloid fibril, pH